2006
DOI: 10.1002/clc.4960290508
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin produced in coronary circulation regulates coronary flow reserve in nondiabetic patients with angiographically normal coronary arteries

Abstract: SummaryBackground: Epicardial adipose tissue expresses adiponectin protein, and its expression is significantly lower in patients with severe coronary artery disease (CAD) than in those without CAD. Transcoronary adiponectin levels are significantly decreased in nondiabetic but not in diabetic patients with CAD. Adiponectin is also an important adipocytokine that is linked to insulin resistance and reduces coronary microvascular function.Hypothesis: Adiponectin may play a significant role in the localized coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…A 2008 study demonstrated that local production of adiponectin by microvascular endothelial cells might be involved in the regulation of cardiac function in the diabetic rat heart 56. Similar results were also found in humans; adiponectin levels were found to correlate with microvascular coronary function and coronary blood flow in different regions of the myocardium 57. The possibility exists, therefore, that inflamed microvascular networks are not only directly affected by, but also contribute to, the generalized loss of physiological adiponectin levels in metabolic disease states.…”
Section: Adiponectin and The Microvasculaturementioning
confidence: 77%
“…A 2008 study demonstrated that local production of adiponectin by microvascular endothelial cells might be involved in the regulation of cardiac function in the diabetic rat heart 56. Similar results were also found in humans; adiponectin levels were found to correlate with microvascular coronary function and coronary blood flow in different regions of the myocardium 57. The possibility exists, therefore, that inflamed microvascular networks are not only directly affected by, but also contribute to, the generalized loss of physiological adiponectin levels in metabolic disease states.…”
Section: Adiponectin and The Microvasculaturementioning
confidence: 77%
“…In obesity, adiponectin levels are decreased (Arita et al 1999), contributing to reduced vascular function (Pilz et al 2005). In the coronary circulation, adiponectin produced by epicardial adipose tissue regulates the cardiac flow reserve (Date et al 2006). …”
Section: Adipokinesmentioning
confidence: 99%
“…19) We previously reported that adiponectin is locally produced in the coronary circulation and might participate in modulating the coronary circulation in individuals with normal coronary arteries. 13) We speculate that adiponectin secreted from epicardial fat directly affects the coronary artery in a vasocrine or paracrine manner. 20) We also reported that patients with CAD had lower adiponectin production in the coronary circulation than non-CAD patients; 14) however, in some patients with CAD, adiponectin in GCV was lower than in LCA, namely the adiponectin-negative production group in the present study.…”
Section: Discussionmentioning
confidence: 89%
“…13) We also reported that signifi cantly less adiponectin was produced locally in the coronary circulation of patients with than without CAD. 14) These fi ndings suggested that lower adiponectin production in the coronary circulation is related to the progression of coronary atherosclerosis; however, there is uncertainty about the association of adiponectin production levels in the coronary circulation with CAD and MACE.…”
mentioning
confidence: 84%